Serat Eksentrik pada Kulit Kayu Marobamban Eccentric Fiber in the Bark of Marobamban - Agus Sulistyo Budi; Nani Husein (Masyarakat Peneliti Kayu Indonesia, 2006)
Type and dimension of cell, especially fiber and tracheid, generally is used as a standard of utilization and quality of product. Beside type and the presence of fiber, up to now unusual fiber dimension in the bark of Marobamban (Helicia spp.), is not yet discovered. Traditionally, this swamp species is planted merely for protecting land from erosion, but the other part of the trunk like bark and its fibers are not yet utilized. The aim of this research is to know the anatomical structure of Marobamban bark and the presence of unusual fiber dimension as well as the fiber class quality. This research was conducted in Wood Anatomy and Identification Laboratory Forestry Faculty, Mulawarman University for one month. IAWA (International Association of Wood Anatomist) is used as observation and analysis standard. The result shows that outer bark with grey white coloured has thorny fiber along the surface and hooks to each other. Fiber length is classified as short category with big diameter. Fiber lumina and wall thickness are classified to moderate and very thick walled respectively. Fiber quality is classified to the third class.